The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.4103/2152-7806.101788
|View full text |Cite
|
Sign up to set email alerts
|

Management of intracranial meningiomas in Enugu, Nigeria

Abstract: Background:Meningiomas may range on presentation from incidentally identified small lesions to large symptomatic tumors in eloquent areas of the brain. Management options correspondingly vary and include careful observation, surgical excision, and palliative application of very limited therapeutic maneuvers in select cases. This paper discusses the options and difficulties in the management of meningiomas in a developing country.Methods:This study is a retrospective analysis of prospectively recorded data of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…On the overall scale, however, the higher proportion of meningioma in this study is also similar to the pattern of brain tumors seen in Nigeria and some other parts of Africa where published reports in the past two decades show a trend toward higher incidences of meningioma relative to gliomas. [ 6 7 15 16 ] Although factors such as life expectancy should be considered, the relative low glioma incidence from this study compared with the Western countries where glioblastoma prevalence is very high, especially among the elderly might suggest racial differences. [ 11 ] This study observed a very low incidence of tumors among the elderly, an age range where the incidence of gliomas should be high.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the overall scale, however, the higher proportion of meningioma in this study is also similar to the pattern of brain tumors seen in Nigeria and some other parts of Africa where published reports in the past two decades show a trend toward higher incidences of meningioma relative to gliomas. [ 6 7 15 16 ] Although factors such as life expectancy should be considered, the relative low glioma incidence from this study compared with the Western countries where glioblastoma prevalence is very high, especially among the elderly might suggest racial differences. [ 11 ] This study observed a very low incidence of tumors among the elderly, an age range where the incidence of gliomas should be high.…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 5 ] More recent reports from sub-Saharan Africa suggest an increasing incidence of meningioma among the brain tumors in the past two decades. [ 3 6 7 ] These findings are strikingly different from the Caucasians, where gliomas, especially glioblastoma predominate. It has been argued that the results from sub-Saharan Africa concerning the epidemiology of ICTs may have been influenced by factors such as shorter life expectancy, poor hospital attendance habit, sociocultural factors that may delay patient decision to seek expert care, dearth of expertise, and relevant facilities needed for proper diagnosis of brain tumors.…”
Section: Introductionmentioning
confidence: 98%
“…In Mezue’s (2012) series of 74 patients with meningiomas, symptoms included; headaches (67.3%), seizures (40.4%), and visual impairment (38.5%), along with increased motor/sensory deficits [Table 2]. [6] For the 100 recurrent meningiomas from Alvernia et al . 2011 series, the authors reviewed of the Karnofsky Performance Scale scores before and after secondary surgery; 92.6 ± 4.6 and 97.9 ± 2.2 [Table 1].…”
Section: Introductionmentioning
confidence: 99%
“…More females than males develop cranial meningiomas, with ratios varying from 1.08:1 to 2.4:1 to 3:1 [Table 2]. [3,6,10] The average age for all patients undergoing cranial surgery for meningiomas ranged from 49.6 – 64 years of age; males were typically in their fifties (average age 57.6), while females were usually in their late fifties/early sixties (average age 59.5) [Table 2]. [3,6,10]…”
Section: Introductionmentioning
confidence: 99%
“…The surgery may damage the cortex in the functional area or affect the gyrus veins in the cortex, which greatly increases the risks of postoperative disability and severe surgical complications. 10 , 11 Therefore, the key is that microtechnique should be used to process the central sulcus vein and the affected sagittal sinus.…”
Section: Discussionmentioning
confidence: 99%